Development and optimization of technology of soft cheese production from camel milk - Gabrilyants, Eleonora; Utebaeva, Aidana; Alibekov, Ravshanbek (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is the soft cheese production from camel milk (Camelus dromedarius), with a specific focus on curd formation and the structural and quality characteristics of the final product. The study addresses a key problem, namely it’s the weak gelation and unstable curd structure of camel milk, resulting from its atypical protein composition, which complicates its use in cheese making. The main task was to identify optimal values of coagulant dose and coagulation temperature to enhance both cheese yield and quality. Experimental studies evaluated the effects of ChyMax® M 1000 at doses of 0.05–0.20 ml/l and coagulation temperatures of 34–40°C on key technological indicators such as yield, syneresis, moisture retention, and textural attributes. Both factors significantly influenced the development of curd and final product quality. The most favorable results were obtained at a coagulant dose of 0.10–0.15 ml/l and a coagulation temperature of 36–38°C. Under these conditions, cheese yield reached up to 184.5 g/l, with improved moisture content (up to 60.5%), moderate syneresis, and enhanced textural characteristics. These outcomes are attributed to increased proteolytic activity and improved gel matrix formation at the optimal conditions. The key distinguishing feature of the results is the identified balance of coagulant dose and temperature, which led to stable curd structure and higher cheese yield. A technological scheme for the soft cheese production from camel milk was developed, offering potential for industrial-scale application. The proposed process is suitable for dairy enterprises seeking to diversify their product range with functional and regionally adapted soft cheeses based on camel milk